Characterization of halide perovskite/titania interfaces as a function of the interlayer composition: A theoretical study. (March 2020) - Shalmashi, Kazhal; Khosravi, Heidar; Boochani, Arash; Azar, Yavar T.
Abstract: In this study, we investigated the electronic structure of halide perovskite/titania interfaces using first-principle methods. Based on the different possible terminations of methylammonium (MA)PbI 3 slabs, we investigated two different models comprising MAI/titania and PbI/titania interfaces. In the case of MAI/titania, a new interface model was built due to the possibility of MA cation deprotonation. We also analyzed the key role of the built-in electric field strength in the cell efficiency and the significant effect of deprotonation on the level alignment. Moreover, we investigated band gap narrowing and level alignment as functions of the compositions of the outermost layers. Our findings may have applications in band engineering and they provide a deeper understanding of the atomistic characteristics of perovskite-based photovoltaic and optoelectronic devices. Highlights: Interlayer composition and band alignment linked in perovskite/titania interfaces. PbI-terminated perovskite/titania interface more stable than MAI/titania. PbI/titania interface level alignment better than that for MAI/titania. Proton-induced downshift of conduction band for TiO 2 affects band alignment.